Gamification's Influence on Tokopedia E-Commerce Repurchase Intentions - Muhammad Nur Afiat; Syamsu Rijal; Rifani Akbar Sulbahri; Fachrurazi, Fachrurazi (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to examine the effect of gamification with the indicators studied consisting of rewards, points, levels and leaderboards on the use of e-commerce applications and repurchase intentions. This research method is quantitative with data collection techniques using survey techniques using questionnaires. The sampling technique uses a purposive sampling technique. The research sample was 97 Business Management Students at Bandung Islamic University. The results of the study show that gamification has a positive effect on the use of e-commerce applications, while it has no effect on repurchase intention. The results also show that the use of e-commerce applications has a positive effect on repurchase intentions in e-commerce.